PENGARUH PERCEIVED EASE-OF-USE, PERCEIVED USEFULNESS, TRUST DAN PERCEIVED ENJOYMENT TERHADAP REPURCHASE INTENTION (STUDI KASUS PADA WEBSITE ZALORA INDONESIA) - INDAH PUSPITASARI; VITA BRILIANA (Jurnal Bisnis dan Akuntansi, 2017)
The purpose of this research is to know the influence of perceived ease of use, perceived usefulness, trust, and enjoyment with repurchase intention at Zalora Indonesia. The research design used in descriptive research and causality research. The population of this research is customers of Zalora Indonesia. The sampling in the study was purposive sampling and uses 100 responded. The respondents of this study were women who make online purchases through the website www.zalora.co.id. Data were analyzed using multiple regression analysis. The result showed that there is an influence among perceived ease of use, perceived usefulness, trust, and perceived enjoyment with repurchase intention at Zalora Indonesia.